Apical Sealing Quality of In Vitro Apicectomy Procedures After Using Both Er:YAG and Nd:YAG - Leonardi, Denise Piotto; Sivieri-Araujo, Gustavo [UNESP]; Zielak, Joao Cesar; Baratto-Filho, Flares; Moriyama, Lilian Tan; Camargo Villela Berbert, Fabio Luiz [UNESP] (Mary Ann Liebert, Inc., 2010)
The aim of this study was to evaluate the apical sealing of dentinal tubules after root-end surface cutting by using Er:YAG and Nd:YAG lasers. After root-canal instrumentation and filling, apices of 50 extracted maxillary canine human teeth were resected by Er: YAG with 400 mJ, 10 Hz, for 30 sec. The samples were randomly assigned to five groups (n = 10): (GI) treated without root-end cavity, but with Nd: YAG (1.0W, 10 Hz, 20 sec) for dentinal tubules sealing; (GII) treated with root-end cavity without the use of Nd: YAG; (GIII) treated with root-end cavity and Nd: YAG application; (GIV) treated with root-end cavity made by Er: YAG with no focus and without Nd: YAG application; and (GV) treated without root-end cavity and without Nd: YAG application. The root-end cavities were performed by using Er: YAG at 300 mJ, 10 Hz, for 20 sec. Subsequently, all teeth were waterproofed and immersed in 2% methylene blue for 48 h in a vacuum environment. The samples were longitudinally sectioned, and microleakage was measured. ANOVA and the Fisher LSD test showed that GIV was less susceptible to microleakage than were the other groups (p < 0.05). Interestingly, the use of the Er: YAG with no focus showed superior dentinal tubule sealing in comparison with the other groups, even with or without root-end cavity and Nd: YAG application.